Public, Safety, Risk - Williams, Kaya Naomi (Social justice, 2017)
The article discusses the Pretrial Services agency in New Orleans, Louisiana's administration of criminal justice, including the agency's determination of public safety risk assessments on whether to grant pretrial release or detention for African American defendants. An overview of the debt that defendants incur through their bail bondsmen's offering money for their pretrial release is provided.